A multi-country survey of public support for food policies to promote healthy diets: Findings from the International Food Policy Study - Janelle Kwon; Adrian J. Cameron; David Hammond; Christine M. White; Lana Vanderlee; Jasmin Bhawra; Gary Sacks (BMC, 2019)
Abstract Background Poor diet is a significant contributor to the burden of global disease. There are numerous policies available to address poor diets; however, these policies often require public support to encourage policy action. The current study aimed to understand the level of public support for a range of food policies and the factors associated with policy support. Methods An online survey measuring support for 13 food policies was completed by 19,857 adults in Australia, Canada, Mexico, the United Kingdom (UK) and the United States (US). The proportion of respondents that supported each policy was compared between countries, and the association between demographic characteristics and policy support was analysed using multivariate logistic regression. Results The level of support varied between policies, with the highest support for policies that provided incentives (e.g., price subsidies) or information (e.g., calorie labelling on menus), and the lowest support for those that imposed restrictions (e.g., restrictions on sponsorship of sport events). This pattern of support was similar in all countries, but the level differed, with Mexico generally recording the highest support across policies, and the US the lowest. Several demographic characteristics were associated with policy support; however, these relationships varied between countries. Conclusion The results suggest that support for food policies is influenced by several factors related to the policy design, country, and individual demographic characteristics. Policymakers and advocates should consider these factors when developing and promoting policy options.